Chemical evaluation of foliage of some tropical leguminous trees and shrubs as fodder - O. O., Oduguwa; C. O. N., Ikeobi; B. O., Oduguwa; O. O., Oyedele (Universiti Putra Malaysia Press, 1997)
Foliage of thirteen leguminous species viz: Mzelia africana, Albizia zygia, Baphia nitida, Cassia siamea, Delonix regia, Parkia biglobosa, Samanea saman, Caesalpinia pulcherrima, Cassia mimosoides, Desmodium velutinum, Flemingia macrophylla, Tephrosia bracteolata and T. densiflora were collected from the wild and the Fulani cattle rearers' settlement around Abeokuta, Nigeria. The samples were analysed for their proximate constituents: crude protein {(CP) ether extract (EE), crude fibre (CF), ash and nitrogen free extracts (NFE)} , and the levels of macro- (Ca, P, Mg, K and Na) and micro-mineral (Mn, Cu, Zn and Fe) elements. The mean values of CP, EE, CF, ash and NFE for trees were 15.2 ± 3.5, 5.2±1.7, 17.8±3.7, 6.2±2.2 and 46.8±3.1 % respectively. The corresponding values for the shrubs were 15.4±1.3, 4.1±0.9, 19.3±1.1, 6. 7±1.3 and 46.4±2. 8 %. The foliage analysed contained adequate level of Ca, Mg and Fe for growth of ruminant livestock with mean values of 0.56±0.30%, 0.16±0.08% and 131.1±74.2 ppm respectively for trees and 1.15±O.49%, 0.2 ±0.06% and 88. 7±49.9 ppm for shrubs. The levels of P, Cu, Zn and K in the foliage were inadequate using the NRC recommendations for ruminants (NRC 1981). The respective mean values were 0.09±0.06%, 3.9±3.1 ppm, 19.5±16.4 ppm, and O.07±O.5 %, 3.7±2.6ppm, 21.7±21.6 ppm and 0.21±0.14% for shrubs. The levels of Na (0.11±0.07% for trees; 0.06 0.04% for shrubs) and Mn (96. 0±142.9 ppm for trees; 49.2±27.21 ppm for shrubs) were marginally adequate. It is suggested that more effort be undertaken to conserve these species as they have better nutritive potential than grasses when used as forage in the dry season.